Neutral density estimation in the ASDEX upgrade divertor from deuterium emissivity measurements during detachment and shoulder formation. (20th September 2019) - Agostini, M; Vianello, N; Carraro, L; Carralero, D; Cavedon, M; Dux, R; Naulin, V; Spolaore, M; Wolfrum, E
Abstract: Neutral density distribution in the divertor region of ASDEX Upgrade is estimated in different discharge conditions. The 2D divertor emission of D α and D γ is obtained with a tomographic inversion of their brightness measured by two cameras. From these emissions, 2D maps of neutrals density n 0 can be obtained by a simple model that takes into account both excitation and recombination processes populating deuterium n = 3 and n = 5 levels. In attached discharges, the neutral density n 0 is larger in the inner divertor, and when increasing core n e its maximum moves toward the dome and the outer divertor region. In particular, the modification of the n 0 distribution is studied in plasmas where the mean electron density in the core increases, moving from an attached to a detached phase. In these discharges, the outboard midplane scrape off layer electron density increases and its profile flattens, with the formation of the so called density shoulder . The modification of the neutral density is followed during this evolution, showing that both the shape and the absolute value of the n 0 distribution change in time, suggesting that they play a role in the two phenomena of shoulder formation and detachment. Moreover, in the detached phase, also the recombination contributes to the neutral deuterium emission.